2021
DOI: 10.4103/lungindia.lungindia_537_19
|View full text |Cite
|
Sign up to set email alerts
|

Accidental breakage of needle tip during endobronchial ultrasound-guided transbronchial needle aspiration

Abstract: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is commonly recommended for the diagnosis of mediastinal lymphadenopathy with malignant and nonmalignant etiology. EBUS-TBNA has been preferred over mediastinoscopy because of several advantages such as comparable diagnostic accuracy, safety, cost-effectiveness, and less invasiveness. Hemorrhage, mediastinitis, pneumonia, mediastinal abscess, empyema, lung abscess, pericarditis, and pneumothorax have been reported as major complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Patients should also be placed under general anesthesia to avoid coughs that could interfere with needle retrieval. (4) Previous cases of needle fracture reported the possible causes might be inappropriate handling or misassembly of the bronchoscope or needle [4]. When our patient received the EBUS-TBNA at the outside hospital, the bronchoscopist might target the lymph nodes in the mediastinum for biopsy.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Patients should also be placed under general anesthesia to avoid coughs that could interfere with needle retrieval. (4) Previous cases of needle fracture reported the possible causes might be inappropriate handling or misassembly of the bronchoscope or needle [4]. When our patient received the EBUS-TBNA at the outside hospital, the bronchoscopist might target the lymph nodes in the mediastinum for biopsy.…”
Section: Discussionmentioning
confidence: 91%
“…Previous case reports described the accidental needle fracture or malfunction during the EBUS-TBNA [4]. Most broken needles were found at the main bronchus, carina, or surrounding lymph nodes, retrieved under direct visualization on the bronchoscopy [4]. Ozgul et al [6] reported an accidental needle fracture, with the broken needle finally localized in the transverse colon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations